2016
DOI: 10.18203/2349-2902.isj20163586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and factors affecting surgical outcome of colorectal carcinoma in rural India: a study of 60 cases

Abstract: INTRODUCTIONColorectal cancer (CRC) is the second leading cause of death from cancer in western countries.1 Forty to fifty percent of patients who undergo potentially curative surgery alone ultimately relapse and die of metastatic disease.2 The most important prognostic indicator of survival in early colon cancer is the stage of the tumor, determined by the depth of penetration through the bowel wall and the number of involved lymph nodes.3 Currently 60% of malignant diseases occur in persons over 65 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…5 The rectum and rectosigmoid were the most common sites of colorectal cancer in the study of Tamgadge, et al in India (56.66%). 19 In the study by Smiddy, et where the most common location is the colon. 22 The results showed that the characteristics of of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5 The rectum and rectosigmoid were the most common sites of colorectal cancer in the study of Tamgadge, et al in India (56.66%). 19 In the study by Smiddy, et where the most common location is the colon. 22 The results showed that the characteristics of of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%